Macroeconomic Determinants of Agricultural Sector Growth in Upper Middle-Income Countries: Is Financial Development Relevant? Array - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2022)
The study investigated the determinants of agricultural sector growth in upper middle-income countries using panel data analysis (panel annual data ranging from 2005 to 2020). The impact of the complementarity between financial and human capital development on agricultural sector growth was also explored in the case of upper middle-income countries. Agricultural sector growth was positively and significantly influenced by its own lag under the dynamic generalized methods of moments (GMM) approach. Fixed effects show that financial development had a significant deleterious impact on agricultural sector growth whilst a significant positive relationship running from financial development towards agricultural sector growth was observed under the pooled ordinary least squares (OLS). The dynamic GMM and the pooled OLS indicates that economic growth’s influence on agricultural sector growth was significantly negative. Fixed effects, random effects and pooled effects show that trade openness’s influence on agriculture sector growth was found to be significantly positive. Fixed and random effects noted that population growth had a significant positive impact on agricultural sector growth whilst population growth’s influence on agricultural sector growth was observed to be significantly deleterious. Consistent with majority of available literature, the study observed that the impact of urbanization on agricultural sector growth was significantly positive. Although the results are mixed, the study urges responsible authorities in upper middle-income countries to enact and implement financial development, trade openness, population increase and urbanization enhancement policies to boost agricultural sector production. Further studies can investigate the other different channels through which financial development can enhance agricultural sector growth in upper middle-income countries.